(untitled) (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2024)
This study investigates the complex interplay between religious extremism, blasphemy laws, and societal responses in Pakistan through a detailed analysis of the 2021 Priyantha Kumara incident. The research employs a multi-stakeholder approach to examine how religious interpretations, legal frameworks, and social dynamics contribute to religious intolerance and violence. Through qualitative analysis of historical data, legal documents, and comparative religious studies, the research reveals significant disparities between Islamic teachings of tolerance and contemporary societal reactions to alleged blasphemy. The study finds that blasphemy accusations in Pakistan increased by approximately 1,300% between 1987-2021, with 89 people killed extrajudicially out of approximately 1,500 accusations. The research identifies three critical factors contributing to this trend: misinterpretation of religious texts, inadequate legal safeguards, and societal pressures. Statistical analysis shows that over 70% of blasphemy cases originated in Punjab province, indicating significant regional variations in the application and interpretation of blasphemy laws. Our findings suggest that comprehensive reform requires a three-pronged approach: legal reforms to prevent misuse of blasphemy laws, enhanced religious education to promote accurate scriptural interpretation, and media sensitization to foster religious tolerance. The study proposes specific recommendations for stakeholders, including establishing specialized investigation units, implementing mandatory initial reviews before FIR registration, and developing community-based conflict resolution mechanisms. This research contributes to the growing body of literature on religious extremism and legal reform in South Asia, offering practical insights for policymakers, religious scholars, and civil society organizations working towards promoting religious tolerance and protecting minority rights.